Modern Warfare, Spiritual Health, and the Role of Artificial Intelligence - Konigsburg, Joyce Ann (Religions, 2022)
Modern warfare utilizes artificial intelligence (AI) combined with remotely piloted aircraft (RPA) to enhance battlefield strategy and create advantages against adversaries. Military drones extend the range of combat, which limits risks, thereby minimizing casualties and loss of human life. With onboard AI systems, drones provide more data and facilitate rapid decision-making for greater situational awareness during conflicts. Military leaders also theorize that remote missions would be physically, emotionally, and psychologically easier for drone pilots, thus reducing mental health issues that plague fighter pilots. However, the intersection of AI with military drones creates unique situations of stress and trauma. RPA personnel manifest symptoms of post-traumatic stress disorder (PTSD) that adversely affect their spiritual health and well-being.